(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The turbine generator cooling water system of Sihwa Tidal Power Plant is an economical system in which the cooling water cools the turbine generator through a circulation pump and the rising temperature recirculates heat exchange with seawater through a surface cooler However, as the cooling water facility continues to operate and a long period of time passes, the cooling water quality in the piping deteriorates. In particular, increasing the concentration of Fe ions in the coolant may promote corrosion of circulating pipes, which may reduce the stability of the water turbine generator operation. Even if the coolant whose water quality has deteriorated is replaced, additional cleaning agents must be treated, but chemical treatment was difficult due to concerns over pipe damage. To overcome this, a filtering device for improving the water quality of cooling water was applied. Through the application of filtering devices for about a month, the water quality was improved by reducing the concentration of cooling water Fe ions by about 70%, and the facility maintenance cost was reduced by about 110,000 per year. We can greatly contribute to maintaining the economical cooling water system and securing the operational stability of water turbine generators by applying the cooling water filter.